2022
DOI: 10.3390/ijerph19084856
|View full text |Cite
|
Sign up to set email alerts
|

Working Environment, Personal Protective Equipment, Personal Life Changes, and Well-Being Perceived in Spanish Nurses during COVID-19 Pandemic: A Cross-Sectional Study

Abstract: During the COVID-19 pandemic, nurses have had to face logistical problems related to critical changes in their work environment, the supply of personal protective equipment (PPE), and hard personal life decisions. This study aimed to investigate the changes in the working environment, PPE use, personal lives, and well-being as perceived by nurses in hospitals and primary care centers in Spain, during the COVID-19 pandemic. A descriptive cross-sectional survey study was conducted in April 2020, including 61 pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Appropriate support is essential to alleviate the psychological distress of medical professionals 14 in the context of the pandemic 15 . It has been reported that nurses working in primary care were faced with various stresses of COVID‐19 and they managed to cope with these stresses 16–19 . To provide effective and sufficient support, the multifaceted effects of the COVID‐19 disaster, from workplace and community and family, and the process by which they have struggled with these difficulties should be described more from various perspectives 20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate support is essential to alleviate the psychological distress of medical professionals 14 in the context of the pandemic 15 . It has been reported that nurses working in primary care were faced with various stresses of COVID‐19 and they managed to cope with these stresses 16–19 . To provide effective and sufficient support, the multifaceted effects of the COVID‐19 disaster, from workplace and community and family, and the process by which they have struggled with these difficulties should be described more from various perspectives 20 …”
Section: Introductionmentioning
confidence: 99%
“…15 It has been reported that nurses working in primary care were faced with various stresses of COVID-19 and they managed to cope with these stresses. [16][17][18][19] To provide effective and sufficient support, the multifaceted effects of the COVID-19 disaster, from workplace and community and family, and the process by which they have struggled with these difficulties should be described more from various perspectives. 20 This study aimed to investigate two research questions: (i) How were nurses engaged in primary care psychologically and socially affected by the COVID-19 disaster?…”
Section: Introductionmentioning
confidence: 99%